2011
DOI: 10.1007/s11274-011-0910-4
|View full text |Cite
|
Sign up to set email alerts
|

Chitooligosaccharides antagonize the cytotoxic effect of glucosamine

Abstract: Chitooligosaccharides (COS) are partially hydrolyzed compounds derived from chitosan that exhibit a number of biological activities, including antitumor, antibacterial and antifungal properties. In this work, we examined the cytotoxicity of pure COS and oligomers A, B and C (solutions composed of different amounts of COS) produced by enzymatic hydrolysis using a crude enzyme extract produced by the fungus Metarhrizium anisopliae. The antiproliferative effect of these molecules was analyzed using tumor cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…The HepG2 cells, when treated with the chitooligosaccharides at a concentration of 0.2 mg/mL, induced cell viability of around 20% and at higher concentrations, it remained practically unaltered. These results corroborate literature data, in that chitooligosaccharides did not show any activity against Hep3B cells [14,15].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The HepG2 cells, when treated with the chitooligosaccharides at a concentration of 0.2 mg/mL, induced cell viability of around 20% and at higher concentrations, it remained practically unaltered. These results corroborate literature data, in that chitooligosaccharides did not show any activity against Hep3B cells [14,15].…”
Section: Resultssupporting
confidence: 92%
“…Similar results were found by Jeon and Kim [16], where chitooligosaccharides inhibited uterine tumors in rats by 73.6%. The modified chitooligosaccharides used in HeLa cells showed an IC 50 value of 0.45 mg/mL [14] and similar results were found in this study, where IC50 was 0.67 mg/mL. Kim and Rajapakse [12] observed that a mixture of chitosan oligomers from tetramer to pentamer could inhibit tumor cell growth in rats.…”
Section: Resultssupporting
confidence: 87%
“…The degradation of chitin into oligosaccharides has promise that may be useful in numerous biological functions, such as antimicrobial activity and antitumor activity [135]. At present, chitooligosaccharides are mainly produced through chemical reactions in industry.…”
Section: Chitinasementioning
confidence: 99%
“…A large number of researchers combine PEI with siRNA to form various siRNA-polymers because of the high-density positive charge of PEI [7,8], however, PEI has high toxicity [28]. On the other hand, CSO is biodegradable and has low toxicity [29]. It has also been reported that CSO has the function like antibiotic, antivirus, antitumor, decreasing blood lipids, hypoglycemic and anti-aging activities [30].…”
Section: Introductionmentioning
confidence: 99%